MANAJEMEN BISNIS SYARIAH SEBAGAI UPAYA MERAIH RIZKI YANG BERKAH: SEBUAH ARTIKEL ULAS BALIK - Karsidi Karsidi; Bambang Sunarko; Ashari Ashari (Faculty of Economics and Business Universitas Jenderal Soedirman, 2016)
Islam teaches and recommends us to do all the things in the life seriously and or-derly based on the norms established by the religion. Management means to regulate all the things in order to be well done, precise, in good order, and complete. This activity is declared in Islamic Doctrines. Therefore, if a business is carried out by the guidance of the norms of the Declared-Islamic Doctriness, the business will not only persue the ma-terial benefits,but also will hope the Favor and the Bless of Alloh/God. The business that is carried out based on the law of Islam is then termed by the Syariah Business Manage-ment. The material benefit gained from this business will have favor of Alloh/God and has the grant of Alloh/God in it.